Role of Aprotinin in Moderate and Severe Burns - Bhatnagar, Prateek; Singh, A. K.; Tarachand, Tarachand (Indian Journal of Plastic Surgery, 1987)
The role of Aprotinin (Antagosan) in moderate and severe thermal burns has been studied. Patients were randomized in two groups; both receiving same treatment with the exception that patients in trial group received Aprotinin in addition. 2000,000 K.I.U. (Kallikrein inhibition units) Aprotinin was given I.V. stat, followed six hourly, for three days. Mortality was 27.08 percent in trial group and 47.9 percent in control group (p < 0.05). Aprotinin is believed to be helpful in reducing mortality in burns.